2007
DOI: 10.1074/jbc.m609906200
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Association of Glutathione Transferase to the Nuclear Membrane

Abstract: The possible nuclear compartmentalization of glutathione S-transferase (GST) isoenzymes has been the subject of contradictory reports. The discovery that the dinitrosyl-diglutathionyl-iron complex binds tightly to Alpha class GSTs in rat hepatocytes and that a significant part of the bound complex is also associated with the nuclear fraction (Pedersen, J. Z., De Maria, F., Turella, P., Federici, G., Mattei, M., Fabrini, R., Dawood, K. F., Massimi, M., Caccuri, A. M., and Ricci, G. (2007) J. Biol. Chem. 282, 63… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 40 publications
6
29
0
1
Order By: Relevance
“…(a) In the male rat liver, Alpha and Mu GSTs are 43 and 56%, respectively (29,30). These values were confirmed for our male rat liver preparations by means of high pressure liquid chromatography (31). (b) Specific activities of Alpha and Mu GSTs are 16 and 22 units/mg, respectively.…”
Section: Theoretical Inhibition Of the Cytosolic Gstssupporting
confidence: 76%
See 1 more Smart Citation
“…(a) In the male rat liver, Alpha and Mu GSTs are 43 and 56%, respectively (29,30). These values were confirmed for our male rat liver preparations by means of high pressure liquid chromatography (31). (b) Specific activities of Alpha and Mu GSTs are 16 and 22 units/mg, respectively.…”
Section: Theoretical Inhibition Of the Cytosolic Gstssupporting
confidence: 76%
“…Unexpectedly, after treatment with 10 mM KCN to displace the complex (9), we find considerable GST activity associated with these components (not shown). The accompanying paper (31) demonstrates that the EPR signal is entirely because of the DNGIC-GST species and that significant amounts of GSTs, mainly GSTA1-1 and GSTA2-2, are associated with the nucleus.…”
Section: Dndgic-gst Interaction In Rat Livermentioning
confidence: 88%
“…In fact, ϳ30% of the entire pool of AlphaGSTs is concentrated near the inner and outer nuclear envelope, forming, as with many other enzymes, a defense barrier for DNA termed "nuclear shield" (31,32). For this peculiar role, some Alpha GSTs developed an extraordinary affinity during evolution but, as it appears, at the expense of their catalytic efficiency.…”
Section: Journal Of Biological Chemistry 26741mentioning
confidence: 99%
“…A peripheral association of P and Mu GST isoforms with the plasma membrane of goat sperm has been described previously (Hemachand et al, 2002). Furthermore, murine GSTA4-4 and several human GSTA isoforms were found to associate with the plasma membrane and outer nuclear membrane, respectively, through electrostatic interactions (Singh et al, 2002;Stella et al, 2007). We have found that GSTP1 is still associated with the plasma membrane after high salt treatment and alkaline carbonate extraction, ruling out the possibilities of electrostatic and/or peripheral interaction of GSTP1 with the plasma membrane.…”
Section: Resultsmentioning
confidence: 76%